Running Windows containers on AWS : a complete guide on successfully running windows containers on Amazon ECS, EKS, and AWS Fargate - Morales, Marcio (Packt Publishing, 2023)
Scale up your Windows containers seamlessly on AWS powered by field-proven expertise and best practices on Amazon ECS, EKS, and Fargate Purchase of the print or Kindle book includes a free PDF eBook Key Features Leverage the most recent best practices to run and manage Windows containers on AWS Learn about AWS tools to containerize and run Windows containers on AWS Deeper understanding on how Amazon ECS, EKS, and Fargate supports Windows containers Book Description Windows applications are everywhere, from basic intranet applications to high-traffic public APIs. Their prevalence underscores the importance of combining the same tools and experience for managing a modern containerized application with existing critical Windows applications to reduce costs, achieve outstanding operational excellence, and modernize quickly. This comprehensive guide to running and managing Windows containers on AWS looks at the best practices from years of customer interactions to help you stay ahead of the curve. Starting with Windows containers basics, you'll learn about the architecture design that powers Amazon ECS, EKS, and AWS Fargate for Windows containers. With the help of examples and best practices, you'll explore in depth how to successfully run and manage Amazon ECS, EKS, and AWS Fargate clusters with Windows containers support. Next, the book covers day 2 operations in detail, from logging and monitoring to using ancillary AWS tools that fully containerize existing legacy .NET Framework applications into containers without any code changes. The book also covers the most common Windows container operations, such as image lifecycle and working with ephemeral hosts. By the end of this book, you'll have mastered how to run Windows containers on AWS and be ready to start your modernization journey confidently. What you will learn Get acquainted with Windows container basics Run and manage Windows containers on Amazon ECS, EKS, and AWS Fargate Effectively monitor and centralize logs from Windows containers Properly maintain Windows hosts and keep container images up to date Manage ephemeral Windows hosts to reduce operational overhead Work with the container image cache to speed up the container's boot time Who this book is for This book is targeted towards DevOps engineer, SREs, solution architects, or a Windows sysadmin who wants to learn more about running Windows containers on AWS. In order to learn from this book, you should have a basic understanding of containers, Docker, and Kubernetes. The book is also beneficial for Windows application developers who want to explore how to achieve better application scalability using containers as a compute layer.